2014
DOI: 10.1007/s11274-014-1657-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of aflatoxin B1 in contaminated rice straw by Pleurotus ostreatus MTCC 142 and Pleurotus ostreatus GHBBF10 in the presence of metal salts and surfactants

Abstract: Aflatoxin B1 (AFB1) is a highly toxic fungal metabolite having carcinogenic, mutagenic and teratogenic effects on human and animal health. Accidental feeding of aflatoxin-contaminated rice straw may be detrimental for ruminant livestock and can lead to transmission of this toxin or its metabolites into the milk of dairy cattle. White-rot basidiomycetous fungus Pleurotus ostreatus produces ligninolytic enzymes like laccase and manganese peroxidase (MnP). These extracellular enzymes have been reported to degrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…(iv) Reduction and oxidation: AFB 1 (1) was converted to AFB 2a (133), which was also called dihydrohydroxyaflatoxin B 1 , by Pleurotus ostreatus GHBBF10. AFB 2a (133) was 200 times less toxic than AFB 1 (1) [108].…”
Section: Detoxification Of Aflatoxinsmentioning
confidence: 86%
See 1 more Smart Citation
“…(iv) Reduction and oxidation: AFB 1 (1) was converted to AFB 2a (133), which was also called dihydrohydroxyaflatoxin B 1 , by Pleurotus ostreatus GHBBF10. AFB 2a (133) was 200 times less toxic than AFB 1 (1) [108].…”
Section: Detoxification Of Aflatoxinsmentioning
confidence: 86%
“…Aflatoxin B 1 (AFB 1 , 1) was converted to dihydrohydroxyaflatoxin B 1 (133), which was also named as aflatoxin B 2a (AFB 2a ), via reduction and oxidation by Pleurotus ostreatus GHBBF10 ( Figure S68) [108]. AFB 1 (1) was detoxified to aflatoxin D 1 (AFD 1 , 134), aflatoxin D 2 (AFD 2 , 135) and aflatoxin D 3 (AFD 3 , 136) through hydrolysis, decarboxylation, and oxidation-reduction by Pseudomonas putida, which was isolated from sugarcane ( Figure S69).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…A number of studies have evaluated intrinsic factors, including carbon source [26,34], nitrogen source [26,34,88], vitamins [26], metals ions [12,34,46,89,90,91,92,93], enzyme inhibitors and promoters [52,89,90,91,92,93,94], initial concentration of mycotoxins [93,95], initial concentration of cells [53,95] and initial pH value [12,14,17,26,31,34,41,46,54,60,88,89,95,96], as well as extrinsic factors, including temperature [12,14,17,25,26,31,34,38,41,46,52,54,60,88,89,95,96], aeriation (shaking rate) [26], oxygen preference [14], as well as pre-incubation [26] and incubation time [34,97]. The experimental designs and optimized biotransformation conditions are summarized in Table 2.…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…Wang et al (2011) and Yehia (2014) used manganese peroxidases from Phanerochaete sordida and P. ostreatus , respectively, to degrade AFB 1 in ex situ experiments. In a microcosm study, Das et al (2014) demonstrated enhanced degradation of AFB 1 in rice straw by P. ostreatus in the presence of certain surfactants and metal salts, and identified several potential breakdown products. Two strains of P. ostreatus were also used to degrade AFB 1 in a co-cultivation experiment with Aspergillus flavus on rice straw revealing that one strain demonstrated superior degradation efficiency (Das et al 2015).…”
Section: Introductionmentioning
confidence: 99%